2010
DOI: 10.1128/jb.01140-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Gene Family of Outer Membrane Proteins ( ropB ) in Rhizobium leguminosarum bv. viciae VF39SM and the Role of the Sensor Kinase ChvG in Their Regulation

Abstract: The outer membrane of Gram-negative bacteria represents the interface between the bacterium and its external environment. It has a critical role as a protective barrier against harmful substances and is also important in host-bacteria interactions representing the initial physical point of contact between the host cell and bacterial cell. RopB is a previously identified outer membrane protein from Rhizobium leguminosarum bv. viciae that is present in free-living cells but absent in bacteroids (H. P. Roest, I. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…(8,17). The expression data for the RL3499::gusA fusion in the chvG mutant background suggests that ChvG does play a role in RL399-RL3502 operon expression; however, another factor is required for the induction of the RL3499-RL3502 operon in the presence of peptides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(8,17). The expression data for the RL3499::gusA fusion in the chvG mutant background suggests that ChvG does play a role in RL399-RL3502 operon expression; however, another factor is required for the induction of the RL3499-RL3502 operon in the presence of peptides.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the sensor kinase ChvG regulates expression of the outer membrane protein gene ropB in the closely related strain R. leguminosarum VF39 (17). ChvG is also important in the expression of the homologous ropB in S. meliloti (8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported isolation of a chvG mutant in Rhizobium leguminosarum VF39 and described its role in regulating the ropB outer membrane protein-encoding gene and an operon required for cell envelope integrity and control of cell morphology (RL3499-RL3502) (10,38). We have also found that ChvG is important for induction of the fabXL genes required for biosynthesis of the lipid A very-long-chain fatty acid during growth under membrane stress conditions (E. M. Vanderlinde and C. K. Yost, unpublished data).…”
mentioning
confidence: 99%